A Cocktail Method for Promoting Cardiomyocyte Differentiation from Bone Marrow-Derived Mesenchymal Stem Cells - Qing Gao; Maojuan Guo; Xijuan Jiang; Xiantong Hu; Yijing Wang; Yingchang Fan (Stem Cells International)
A growing body of evidence supports the argument that bone marrow-derived mesenchymal stem cells (MSCs) can differentiate into cardiomyocyte-like cells in an appropriate cellular environment, but the differentiation rate is low. A cocktail method was designed: we investigated the role of 5-azacytidine (5-aza), salvianolic acid B (SalB), and cardiomyocyte lysis medium (CLM) in inducing MSCs to acquire the phenotypical characteristics of cardiomyocytes. The fourth-passage MSCs were treated with 5-aza, SalB, CLM, 5-aza+salB, 5-aza+CLM, SalB+CLM, and 5-aza+SalB+CLM for 2 weeks. Immunofluorescence results showed that cTnT expression in the 5-aza+salB+CLM group was stronger than other groups. Real-time qPCR and Western blotting analyses showed that cTnT, alpha-cardiac actin, mef-2c, Cx43, and GSK-3beta expression increased while beta-catenin expression decreased. The salB+5-aza+CLM group had the most evident effects. SalB combined with 5-aza and CLM improved cardiomyocyte differentiation from MSCs. In the MSCs differentiation process, the Wnt/beta-catenin signaling pathway had been inhibited.